Contrast sensitivity function of preschool children. Issue 8 (August 1981) - Atkinson, J.; French, J.; Braddick, O.
Abstract : A procedure specifically adapted for children of preschool age has been used to measure contrast sensitivity in emmetropic children aged 3 to 5 years. Mothers of the children acted as adult observers using the same procedure. The results show that the contrast sensitivity function of adults and children is very similar, sensitivity for the children being slightly lower than that for adults at all spatial frequencies. The sensory and cognitive factors involved in these differences are discussed.